Constructing certainty through public budgeting: budgetary responses to the COVID-19 pandemic in Finland, Norway and Sweden. Issue 5 (20th October 2020) - Argento, Daniela; Kaarbøe, Katarina; Vakkuri, Jarmo
Abstract : Purpose: This paper provides a reflective comparison of the budgetary implications of the COVID-19 pandemic for three Nordic countries: Finland, Norway and Sweden. Design/methodology/approach: By drawing from the notion of ambiguity and constructions of certainty, this study analyzes the most relevant budgetary allocations and packages implemented by the governments of Finland, Norway and Sweden in response to the COVID-19 crisis using empirical documentary data. Findings: Influenced by the need to save citizens' lives and protect the economy, the three countries have interpreted the COVID-19 threat in different ways. While Finland and Norway seem to be fighting a war against the virus, Sweden appears to view COVID-19 as an exceptionally difficult flu. These different perspectives are reflected in the strategies and budgetary responses implemented in the three countries. Originality/value: By elaborating on the ambiguities of reality, causality and intentionality, this paper shows how the budgeting mindset aimed at creating certainties among citizens varies among the Nordic countries, which are generally assumed to be similar.